Identification of QTLs/Defense Genes Effective at Seedling Stage Against Prevailing Races of Wheat Stripe Rust in India - Pradhan, Anjan Kumar; Kumar, Sundeep; Singh, Amit Kumar; Budhlakoti, Neeraj; Mishra, Dwijesh C.; Chauhan, Divya; Mittal, Shikha; Grover, Monendra; Kumar, Suneel; Gangwar, Om P.; Kumar, Subodh; Gupta, Arun; et al. (Frontiers in Genetics, 2020)
Resistance in modern wheat cultivars for stripe rust is not long lasting due to narrow genetic base and periodical evolution of new pathogenic races. Though, nearly 83 Yr genes conferring resistance to stripe rust have been cataloged so far, hardly few of them have been mapped and utilized in breeding programs. Characterization of wheat germplasm for novel sources of resistance and their incorporation into elite cultivars is required to achieve durable resistance and thus, to minimize the yield losses. Here, a genome-wide association study (GWAS) was performed on a set of 391 germplasm lines with the aim to identify quantitative trait loci (QTL) using 35K Axiom® array. Phenotypic evaluation disease severity against four stripe rust pathotypes i.e., 46S119, 110S119, 238S119 and 47S103 (T) at the seedling stage under glass house providing optimal conditions was carried out consecutively for two years (2018 and 2019 winter season). Association study revealed that a total of 40 QTLs were signiﬁcantly associated with seedling-plant resistance to stripe rust. Out of these, 20 QTLs were found to be closely linked with previously reported yellow rust resistance genes/QTLs on chromosomes 1B, 2B, 5B and 6B while 20 novel QTLs were mapped on chromosomes 2D, 3A, 3D, 5A and 7D. These 20 novel QTLs identified in the present study might play a key role in marker-assisted breeding for developing stripe rust resistant wheat cultivars.